2020
DOI: 10.1590/0100-29452020530
|View full text |Cite
|
Sign up to set email alerts
|

Changes in leaf nutrient content and quality of pear fruits by biofertilizer application in northeastern Italy

Abstract: The aim of this study was to verify the influence of biofertilizer application resulting from energy production from corn biomass on nutrient uptake by pear plants during the growing cycle, and on fruit quality. The experiment was carried out on a Siltic Haplic Calcisol in the Italian province of Ferrara, in a medium-density Abbé Fétel commercial orchard. Treatments consisted of control (no application) and biofertilizer (30 m3 ha-1 biofertilizer application on the row), with four replicates. The following var… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
3
0
1

Year Published

2020
2020
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(5 citation statements)
references
References 51 publications
1
3
0
1
Order By: Relevance
“…Hence, Mg supplementation can effectively alleviate this effect and promote the tobacco growth under cold stress, and may contribute to increase in biomass of tobacco plant. The current study also showed the interesting results of higher root and shoot nutrients contents under +Mg treatment compared with -Mg for cold stress (Figure 3), suggesting the relevance of the causeeffect relationship between temperature and nutrients contents, and this effect was enhanced in the presence of Mg, and line with previous findings (Soniya et al, 2018;Dietrich et al, 2020;Perazzoli et al, 2020;Geng et al, 2021). The nutrient uptake takes place primarily through root interception (Onwuka and Mang, 2018), and the addition of Mg has a positive effect on root length, and as a result, nutrient uptake is increased (Huang et al, 2021).…”
Section: Discussionsupporting
confidence: 91%
“…Hence, Mg supplementation can effectively alleviate this effect and promote the tobacco growth under cold stress, and may contribute to increase in biomass of tobacco plant. The current study also showed the interesting results of higher root and shoot nutrients contents under +Mg treatment compared with -Mg for cold stress (Figure 3), suggesting the relevance of the causeeffect relationship between temperature and nutrients contents, and this effect was enhanced in the presence of Mg, and line with previous findings (Soniya et al, 2018;Dietrich et al, 2020;Perazzoli et al, 2020;Geng et al, 2021). The nutrient uptake takes place primarily through root interception (Onwuka and Mang, 2018), and the addition of Mg has a positive effect on root length, and as a result, nutrient uptake is increased (Huang et al, 2021).…”
Section: Discussionsupporting
confidence: 91%
“…In some apple cultivars, it was noted that a higher dry matter content was related to higher flesh firmness [34]. However, in this trial, no relations between fruit dry matter and flesh firmness were observed, providing more similar results to those found in pear and cactus pear [35,36]. Soluble solid content (SSC) represents another important quality parameter, highly related to fruit consumer acceptance (Table 1).…”
Section: Effects Of Water Reduction On Fruit Qualitymentioning
confidence: 51%
“…As hortaliças folhosas respondem bem a adubação orgânica e consequentemente, apresentam maior aporte em suas características agronômicas (OLIVEIRA et al, 2010). No entanto, é preciso considerar o cultivo sucessivo, que promove maior resultado em consequência da mineralização promovida Revista Verde, v.15, n.4, p.346-352, 2020 pelos micro-organismos que habitam o solo (ZIECH et al, 2014;PINHEIRO et al, 2019).…”
Section: Resultsunclassified